Career effects of taking up parental leave. Evidence from a Dutch University - Jan Dirk Vlasblom; Janneke Plantenga (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2010)
In this paper we study the effect of parental leave on individual careers. We use individual registration data of a Dutch non-profit firm (Utrecht University). Our outcomes show that even with a short period of flexible leave there are career effects. More specifically, these effects are not unambiguously positive: slightly longer job durations are found, but also a lower probability of wage increases. It also appears that there are differences in effects between men and women: for men the effects appear to be smaller and of a more temporary character than for women. Apparently, even in a highly flexible system as the Dutch, with a high take up rate of men, the labour-care balance is still not gender neutral and not career neutral.
Keywords: 330; Parental leave; Labour force participation; Labour career; Gender